(untitled) (Latin-American Journal of Computing, 2020)
This article presents the process of developing eportfolios management software and the results obtained through its use in a subject. The software focuses mainly on personalizing learning in university context. For this, the system takes into account both the different levels of assimilation of knowledge that a student can achieve and indicators that give the teacher a guideline of progress in the learning process. With the work, authors wants to provide support to teachers in the learning process, through the proposal of a learning path to achieve the highest possible levels of learning for a particular student through the use of learning materials adapted to each situation.